Diagnosis of switch faults in three phase inverters using neural network - Bai, Haonan (2013)
Power electronics-based inverters are high performance, high-cost electric power conversion devices. Meanwhile they are the major components in industrial and automotive electric drives. However, power electronics inverters can be considered to be the weakest link in such systems because of the higher probability of failures of switches. So their safe and stable operation directly affects production efficiency and quality.